Spinal subdural haematoma in von Willebrand disease - Franko, Artur (Radiology and oncology (Ljubljana), 2009)
Background. Von Wilebrand disease (vWD) is the most common inherited disorder of hemostasis. Bleeding in patients with von Wilebrand disease is a frequentlyreported complaint. Patients with inherited bleeding disorders are also in a large number of cases infected with hepatitis C virus (HCV). Studiesshowed an increased risk factor for intracerebral hemorrhage (ICH) in patients infected with HCV receiving the combination treatment. Case report. A44-year old man reported to our Emergency Department with low back pain, headaches, neck pain, leg weakness and urinary retention. The neurological examination showed nuchal rigidity and spastic paraparesis. Thoracic spine MRIrevealed a subacute subdural haematoma at T8-T11 level. Conclusions. To thebest of our knowledge, this is the first report of a subdural haematoma of the thoracic spine in a patient with vWD and chronic HCV infection. The presented patient was receiving a combination treatment, a fact that has also to be taken in consideration as a possible risk factor for a bleeding episode.
Keywords: hematom; Hematom subduralni; Hematoma, Subdural; Hepatitis C; hrbtenica; Hrbtna vretenca; krvavitev; Middle Age; motnje; Srednja leta; strjevanje krvi; Thoracic Vertebrae; von Willebrandova bolezen; Von Willebrand's Disease